Mesopotamian eye disease texts: the Nineveh treatise - Geller, Markham J. (Die babylonisch-assyrische Medizin in Texten und Untersuchungen, 2020)
There is to date no comprehensive treatment of eye disease texts from ancient Mesopotamia, and no English translation of this material is available. This volume is the first complete edition and commentary on Mesopotamian medicine from Nineveh dealing with diseases of the eye. This ancient work, languishing in British Museum archives since the 19th century, is preserved on several large cuneiform manuscripts from the royal library of Ashurbanipal, from the 7th century BC. The longest surviving ancient work on diseased eyes, the text predates by several centuries corresponding Hippocratic treatises. The Nineveh series represents a systematic array of eye symptoms and therapies, also showing commonalities with Egyptian and Greco-Roman medicine. Since scholars of Near Eastern civilizations and ancient and general historians of medicine will need to be familiar with this material, the volume makes this aspect of Babylonian medicine fully accessible to both specialists and non-specialists, with all texts being fully translated into English